(untitled) (Journal of Humanitarian and Applied Sciences, 2020)
In recent years, much consideration has been devoted to the newly developed methods to construct analytic solutions of non-linear difference equations. One of these reliable methods is the Differential Transform Method DTM which has been used extensively to solve different types of linear and non-linear problems. In this paper, we explore the potential of using the DTM to solve rational difference equations and identify new open problems and conjectures of this kind.